Bridging the gap: United World College students' initiatives in work with refugees - Katja della Liberia; Ramita Ratsathanuwati; Everdina Vermaat (Scottish Journal of Residential Child Care)
The refugee crisis is global. Many aspects of our daily lives are touched by this, especially those who work with people every day. Child care assumes a more important role than ever, being the institution where integration happens first for unaccompanied asylum seeking children and young people. We, students of one of 15 United World Colleges (UWCs), encounter the topic on a daily basis – be it through direct experiences of our friends, our work in service projects or discussions we have as a school community. So it appears quite logical for us to give this a bigger role in our daily lives, and learn about new ways to engage with and improve communication between various groups of people.